Characterization of various zinc oxide catalysts and their activity in the dehydration–dehydrogenation of isobutanol - MARY RIAD; LAMIA SAAD (Journal of the Serbian Chemical Society, 2008)
Mono and bifunctional zinc oxide catalysts were prepared to study their activity in the catalytic conversion of isobutanol. The prepared catalysts were characterized by X-ray diffraction analysis and nitrogen adsorption measurements. The conversion of isobutanol was taken as a model reaction to measure the catalytic activity of the prepared oxide catalysts. The overall conversion yield of competitive dehydration–dehydrogenation reactions of isobutanol was found to be higher over the binary oxide catalysts than over the single oxide one at all reaction temperature within the range 250–400 °C. The binary oxide catalysts were more selective for isobutene, as the predominant dehydrated product. The single oxide catalyst exhibited higher selectivity towards isobutyraldehyde as the dehydrogenated product, and the selectivity increased with increasing reaction temperature.